Processing Speed Mediates the Longitudinal Association between ADHD Symptoms and Preadolescent Peer Problems - Thorsen, Anders L.; Meza, Jocelyn; Hinshaw, Stephen; Lundervold, Astri J. (Frontiers in Psychology, 2018)
We investigated the relation between dimensional aspects of inattention and hyperactivity-impulsivity in childhood and peer problems four years later, as well as the potential mediating effects of intellectual function. The sample included 127 children (32 with attention-deficit/hyperactivity disorder). Symptoms of inattention and hyperactivity-impulsivity were assessed via parent and teacher reports on Swanson Nolan and Pelham-IV questionnaire. Peer problems were assessed by parent reports on the Strengths and Difficulties Questionnaire, and children’s intellectual functioning by the third edition of the Wechsler Intelligence Scale for Children. Linear regressions showed a significant effect of inattention on future peer problems, partially mediated by slow processing speed. These effects remained significant when ADHD status was covaried. Findings highlight the importance of processing speed in explaining the predictive relation between childhood inattention and later peer problems. Inattention and processing speed in early childhood are potentially malleable factors influencing adolescent social functioning.